2001
DOI: 10.1007/s101890170078
|View full text |Cite
|
Sign up to set email alerts
|

Glassy dynamics of simulated polymer melts: Coherent scattering and van Hove correlation functions

Abstract: We report results of molecular-dynamics simulations of a model polymer melt consisting of short non-entangled chains in the supercooled state above the critical temperature Tc of mode-coupling theory (MCT). To analyse the dynamics of the system, we computed the incoherent, the collective chain and the collective melt intermediate scattering functions as well as their space Fourier transforms, the van Hove correlation functions. In this first part of the paper we focus on the dynamics in the β-relaxation regime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
68
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 65 publications
10
68
0
2
Order By: Relevance
“…The small amplitude of ␣ 2 p (t) may be attributed to the difference in packing of the monomers and of the chains. The monomers of our model exhibit an oscillatory pairdistribution function g(r) 35 whose shape and range are very similar to those found in simple dense liquids. In contrast to that, the pair-distribution function g cm (r) for the centers-ofmass is fairly structureless, and resembles the g(r) of a gas.…”
Section: ͑3͒supporting
confidence: 64%
See 3 more Smart Citations
“…The small amplitude of ␣ 2 p (t) may be attributed to the difference in packing of the monomers and of the chains. The monomers of our model exhibit an oscillatory pairdistribution function g(r) 35 whose shape and range are very similar to those found in simple dense liquids. In contrast to that, the pair-distribution function g cm (r) for the centers-ofmass is fairly structureless, and resembles the g(r) of a gas.…”
Section: ͑3͒supporting
confidence: 64%
“…This is the signature of the slowing down of structural relaxation. Second, the curves collapse in the time window of the minimum which deepens and evolves into a protracted plateau with decreasing T. Previous analysis 34,35,37,38 showed that this time window corresponds to the MCT ␤-process where one expects temporary intermittence of particle motion due to the cage effect. 2, 56 In the ␤-regime, g n (t) is close to the localization length 6r n,c 2 , 2,39,56…”
Section: Mobile End Monomersmentioning
confidence: 88%
See 2 more Smart Citations
“…In the past studies in linear polymers, 17 it was noted that the mean localization length r sc calculated from ⌬r 2 ͑t * ͒ϳ6r sc 2 , when expressed in terms of the intermolecular distance d =2 / Q max ͑Q max represents the magnitude of the first peak of the static structure factor͒ it yields a value of r sc / d Ӎ 0.094 very close to a value of 0.095 that was also found in linear bead-spring models. 9,41,42 A similar estimation of the mean localization length based on the value of r * as calculated from the present models at the low temperature limit results to a value of r sc / d Ӎ 0.109 nearly identical to the Lindemann criterion for melting. 44 To examine the dependence of r * on the location of the beads within the dendrimer structure for a constant dendrimer size, we followed the procedure described above for the g = 1 and g = 2 shells of the G3 model at all the temperatures for which reliable estimations could be performed.…”
Section: -5supporting
confidence: 74%